High export of dissolved silica from the Greenland Ice Sheet. Issue 17 (14th September 2016) - Meire, L.; Meire, P.; Struyf, E.; Krawczyk, D. W.; Arendt, K. E.; Yde, J. C.; Juul Pedersen, T.; Hopwood, M. J.; Rysgaard, S.; Meysman, F. J. R.
Abstract: Silica is an essential element for marine life and plays a key role in the biogeochemistry of the ocean. Glacial activity stimulates rock weathering, generating dissolved silica that is exported to coastal areas along with meltwater. The magnitude of the dissolved silica export from large glacial areas such as the Greenland Ice Sheet is presently poorly quantified and not accounted for in global budgets. Here we present data from two fjord systems adjacent to the Greenland Ice Sheet which reveal a large export of dissolved silica by glacial meltwater relative to other macronutrients. Upscaled to the entire Greenland Ice Sheet, the export of dissolved silica equals 22 ± 10 Gmol Si yr −1 . When the silicate‐rich meltwater mixes with upwelled deep water, either inside or outside Greenland's fjords, primary production takes place at increased silicate to nitrate ratios. This likely stimulates the growth of diatoms relative to other phytoplankton groups. Key Points: The Greenland Ice Sheet functions as an important source of silicate for the fjords and surrounding coastal waters Glacial meltwater does not directly stimulate phytoplankton productivity due to low nitrate concentrations Exported silicate from the Greenland Ice Sheet is taken up by diatoms, suggesting a regulating role in phytoplankton composition